MITIGASI BENCANA DENGAN PEMETAAN RISIKO TANAH LONGSOR DI KECAMATAN DLINGO, KABUPATEN BANTUL - , Agung Permana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dlingo district lies at 7°48'45\"S - 7°54'40\" S and 110°24'19\" E - 110°28'16\" E longitude. Dlingo district located about 25 km southeast of Yogyakarta. Landslides occur several times in District Dlingo. Last landslide events occurred in Muntuk village which resulted in two houses buried on January 3, 2013. This study aims to create a map of landslide risks in the District Dlingo along with suggestions for mitigation. The study includes mapping physical conditions, environmental conditions, land use and population The study was conducted with the interpretation of topographic maps, regional geological maps, and Rupa Bumi Indonesia maps. The study then combined with field observations in the form of detailed geological mapping, landslide-prone locations, and land use and population. The study was based on Regulation of BNPB No. 2 Tahun 2012 on General Guidelines for Disaster Risk Assessment. Analysis was performed using Geographic Information System application ArcGIS 9.3 . Weighting factor score hazard, vulnerabilities and capacities using Analytical Hierarchy Process with the help of the software Expert Choice 11. Map compiled by the specific gravity of the threat of rock, slope, structural geology, rainfall, seismicity and groundwater. Vulnerability map prepared based on economic vulnerability, social, physical and environmental. Map prepared by the capacity of institutional capacity, early warning, and evacuation paths and countermeasures. Map compiled from the combination of the results of the risk map of threats, vulnerabilities and capacities. The results of the study in the form of detailed geological maps and thematic geological maps. This map is then processed into a hazard map. Hazard map produced three hazard zones, namely the high, medium and low hazard. High hazard zones located in the village of Mangunan, Muntuk and Terong dominated by weathered breccia rocks and steep slope. Medium and low threat zone composed of limestone and gentler slope. Vulnerability map provide information three villages included in the zone of high vulnerability, two villages included in the zone of moderate vulnerability and one village being low vulnerability zone. Capacity map shows one village with a high capacity and moderate capacity and four villages with a low level of capacity. Risk map shows zones of high risk relevant to high-hazard zones. It can be said, the hazard factors play a greater role in determining the level of risk of landslides. Mitigation measures that need to be improved is making the evacuation in every village and repair instructions evacuation route. Engineering technique that can be done by reduce the slopes and terraces manufacture. These maps are expected to provide information of physical and environmental conditions associated with landslides in order to assist in preparing the Local Government system more effective disaster mitigation in Bantul.